2013
DOI: 10.1038/nature12339
|View full text |Cite
|
Sign up to set email alerts
|

The role of spin in the kinetic control of recombination in organic photovoltaics

Abstract: In biological complexes, cascade structures promote the spatial separation of photogenerated electrons and holes, preventing their recombination. In contrast, the photogenerated excitons in organic photovoltaic cells are dissociated at a single donor-acceptor heterojunction formed within a de-mixed blend of the donor and acceptor semiconductors. The nanoscale morphology and high charge densities give a high rate of electron-hole encounters, which should in principle result in the formation of spin-triplet exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
613
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 494 publications
(641 citation statements)
references
References 32 publications
23
613
4
1
Order By: Relevance
“…The impact of fullerene nanocrystallinity on charge separation has been noted previously, where it was attributed to high local electron mobility within the traditional Onsager framework 11,30 as well as to shifts in electron affinity of the fullerene crystallites 31 . In contrast, our results here ARTICLE point to the role of delocalization, analogous to recent findings for organic-inorganic HJs 32 , and are consistent with a growing number of recent reports in which charge separation is driven by accessing band-like CT states that subsequently decay on a sub-50 ps timescale (an upper limit based on the resolution of our PL transient data) into separated, free charge carriers 3,4,29,33 . In summary, these results support a model of delocalized CT state dissociation and show that this process depends critically on nanoscale fullerene crystallinity.…”
Section: Discussioncontrasting
confidence: 56%
“…The impact of fullerene nanocrystallinity on charge separation has been noted previously, where it was attributed to high local electron mobility within the traditional Onsager framework 11,30 as well as to shifts in electron affinity of the fullerene crystallites 31 . In contrast, our results here ARTICLE point to the role of delocalization, analogous to recent findings for organic-inorganic HJs 32 , and are consistent with a growing number of recent reports in which charge separation is driven by accessing band-like CT states that subsequently decay on a sub-50 ps timescale (an upper limit based on the resolution of our PL transient data) into separated, free charge carriers 3,4,29,33 . In summary, these results support a model of delocalized CT state dissociation and show that this process depends critically on nanoscale fullerene crystallinity.…”
Section: Discussioncontrasting
confidence: 56%
“…We understand that charge recombination is equally important as charge generation in PSCs, and recent findings suggest that kinetics (rather than thermodynamics) can prevent charge recombination and hence increase the device performance. 27,28 We start with experimental observations of CT states from both absorption and emission measurements. This is followed by spectroscopic evidence that free charge carriers are generated in the range of 100 femtoseconds in highly efficient blends.…”
Section: Introductionmentioning
confidence: 99%
“…In efficient devices, either re-trapping must be suppressed or the trapped CT states that form must themselves be able to separate into free charges. In a recent experiment, Rao et al noted the absence of nongeminate triplet excitons at open circuit in an efficient PIDT-PhanQ:PC 60 BM device 17 . Since three quarters of nongeminate CT states should have triplet character, they concluded that such CT states were able to separate long after exciton dissociation first occurs, thus avoiding the formation of triplet excitons.…”
mentioning
confidence: 99%